Effects of Lysozyme, Proteinase K, and Cephalosporins on Biofilm Formation by Clinical Isolates of Pseudomonas aeruginosa - Mohamed Eladawy; Mohammed El-Mowafy; Mohamed Mohamed Adel El-Sokkary; Rasha Barwa (Interdisciplinary Perspectives on Infectious Diseases)
Pseudomonas aeruginosa is an opportunistic pathogen that can form biofilms, which confer resistance to immune clearance and antibacterial treatment. Therefore, effective strategies to prevent biofilm formation are warranted. Here, 103 P. aeruginosa clinical isolates were quantitatively screened for biofilm formation ability via the tissue culture plate method. The effects of lysozyme (hydrolytic enzyme) and proteinase K (protease) on biofilm formation were evaluated at different concentrations. Lysozyme (30 μg/mL), but not proteinase K, significantly inhibited biofilm formation (19% inhibition). Treatment of 24-hour-old biofilms of P. aeruginosa isolates with 50 times the minimum inhibitory concentrations (MICs) of ceftazidime and cefepime significantly decreased the biofilm mass by 32.8% and 44%, respectively. Moreover, the exposure of 24-hour-old biofilms of P. aeruginosa isolates to lysozyme (30 μg/mL) and 50 times MICs of ceftazidime or cefepime resulted in a significant reduction in biofilm mass as compared with the exposure to lysozyme or either antibacterial agent alone. The best antibiofilm effect (49.3%) was observed with the combination of lysozyme (30 μg/mL) and 50 times MIC of cefepime. The promising antibiofilm activity observed after treatment with 50 times MIC of ceftazidime or cefepime alone or in combination with lysozyme (30 μg/mL) is indicative of a novel strategy to eradicate pseudomonal biofilms in intravascular devices and contact lenses.